Implications of Halal Product Certification For Small and Medium Enterprises in the Food Sector in Angkola Barat District, South Tapanuli Regency - Hasibuan, Hasmiza Sari Amaliya; Surya, Maulana Andi (Universitas Muhammadiyah Sorong, 2025)
This research investigates the implications of halal product certification for micro, small, and medium enterprises (MSMEs) in the food and beverage sector across West Angkola and South Tapanuli Regencies. Using a qualitative case study approach, data was gathered from key informants, including the District Secretary, the Head of the Religious Affairs Office, a Halal Product Certification Process Facilitator (P3H), and MSME business owners, both certified and non-certified.The findings reveal that while MSMEs have a deep conceptual understanding of “halal,” which includes both Shariah principles and the concept of thayyib (good and clean), there is a significant gap between this understanding and the formal procedural knowledge required for certification. Despite government socialization efforts, many MSMEs are reluctant to apply for certification due to a lack of information, a perception of high costs, and time constraints.In contrast, proactive MSMEs are motivated by direct support from P3H facilitators, whose role proves crucial in bridging this knowledge gap. Halal certification brings tangible benefits to MSMEs: it boosts consumer trust and loyalty by serving as a mark of credibility and quality assurance, expands market access locally, regionally, and nationally, and indirectly encourages business owners to improve their business quality and professionalism.The study concludes that socialization alone is insufficient without intensive, personalized facilitation and assistance from parties like P3H. This direct support is essential for helping MSMEs overcome practical barriers and encouraging them to take proactive steps toward obtaining halal certification.